Lightning burns and nerve pain. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
The lightning injuries frequently affect adult males in the summer months. The lightning causes damage due to thermal and electric stimuli, magnetic fields changes etc. and may be responsible for death through irreversible damage of the central nervous system, ventricular fibrillation, paralysis of the respiratory muscles. The skin lesions, often affecting the upper limbs and upper trunk, have irregular, arborescent shape (Lichtenberg figures). The neurological injury may be immediate, transient or persistent, and delayed. Its pathogenesis is not linked to a direct action on the nervous system, which is a poor conductor, but it seems mediated by vascular damage. Alternatively, the nerve damage may be due to excessive free radicals that damage the cell membrane of myelin cells resulting in a demyelinating effect.